THE ROLE OF TRANSFORMATIONAL LEADERSHIP IN ENHANCING TEACHER PROFESSIONALISM AT MTS AD-DARUT TAUHID - Nisa, Khoirun; Wijaya, Candra (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to examine the role of transformational leadership in enhancing teacher professionalism at MTS Ad-Darut Tauhid. The research employs a descriptive qualitative approach, using data collection techniques such as interviews, observations, and documentation involving the head of the madrasah, vice principals, curriculum staff, and teachers. The findings indicate that transformational leadership is implemented through role modeling, motivational support, encouragement of innovation, individual attention, involvement of teachers in decision-making, and developmental supervision. Supporting factors in the implementation of this leadership style include a positive organizational culture and support from stakeholders. In contrast, inhibiting factors consist of limited technological infrastructure and low digital literacy among teachers. This study confirms that transformational leadership not only enhances teacher professionalism but also fosters a collaborative and innovative school environment.